Virgin Coconut Oil: Remedial Effects on Renal Dysfunction in Diabetic Rats. (9th July 2014) - Akinnuga, A. M.; Jeje, S. O.; Bamidele, O.; Amaku, E. E.; Otogo, F. O.; Sunday, V. E.
Abstract : Renal dysfunction is now a prevalent complication of diabetes mellitus. Therefore, this study was carried out to evaluate the remedial effects of virgin coconut oil (VCO) on renal dysfunction in diabetic rats. Fifteen albino Wistar rats were divided into 3 groups that comprise normal control group (Group I) and diabetic control group (Group II) fed with normal rat chows and a diabetic test group (Group III) fed with 10% VCO diet. Group II and Group III were made diabetic by single intraperitoneal injection of 150 mg/kg of freshly prepared alloxan monohydrate. After 72 hours of alloxan injection, fasting blood glucose was tested to confirm diabetes mellitus. After 3 weeks, the animals were anaesthetized and sacrificed to collect blood samples for renal function analysis. The creatinine, urea, and blood urea nitrogen values of Group II were significantly different from those of Group I and Group III atP < 0.001 . Also, there was significant difference (P < 0.05 ) in total protein value between Group II (4.42  ±  0.47 mg/dL) and Group I (5.78  ±  0.12 mg/dL) as well as Group III (5.86  ±  0.19 mg/dL), but there was no significant difference between that of Group I and Group III (5.78  ±  0.12 mg/dL and 5.86  ±  0.19 mg/dL, resp.). Thus, VCO is effective in preventing renal damage in diabetic patients.